Hippocampal size predicts rapid learning of a cognitive map in humans. Issue 6 (18th March 2013) - Schinazi, Victor R.; Nardi, Daniele; Newcombe, Nora S.; Shipley, Thomas F.; Epstein, Russell A.
Abstract The idea that humans use flexible map‐like representations of their environment to guide spatial navigation has a long and controversial history. One reason for this enduring controversy might be that individuals vary considerably in their ability to form and utilize cognitive maps. Here we investigate the behavioral and neuroanatomical signatures of these individual differences. Participants learned an unfamiliar campus environment over a period of three weeks. In their first visit, they learned the position of different buildings along two routes in separate areas of the campus. During the following weeks, they learned these routes for a second and third time, along with two paths that connected both areas of the campus. Behavioral assessments after each learning session indicated that subjects formed a coherent representation of the spatial structure of the entire campus after learning a single connecting path. Volumetric analyses of structural MRI data and voxel‐based morphometry (VBM) indicated that the size of the right posterior hippocampus predicted the ability to use this spatial knowledge to make inferences about the relative positions of different buildings on the campus. An inverse relationship between gray matter volume and performance was observed in the caudate. These results suggest that (i) humans can rapidly acquire cognitive maps of large‐scale environments and (ii) individual differences in hippocampal anatomy may provide the neuroanatomical substrate for individual differences in the ability to learn and flexibly use these cognitive maps. © 2013 Wiley Periodicals, Inc.